Incentive Approach Toward Retaining Cultivated Farmland: A Case of Badung District, Bali Province - Putra, I Wayan Indrabayu Pandi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2014)
Farmland conversion has permanent impact, means that once it converted there will never be a wetland again. It also has continuous pattern as construction and expansion of settlements development will always followed by development of new accessibility where agricultural land that were originally located in remote area, indirectly enjoy benefit in terms of access and eventually soar of land prices. The increasing phenomena of conflict over land show that land has a massive opportunity especially to the urban area which has the dynamic pattern of spatial and social mobility. In order to addressing farmland conversion, many policies and regulations have been issued by Indonesian Government, including the newest one, Law no 41/2009 on Protection of Sustainable Agricultural Land. How far the relevancy of this approach with current regional development is and to what extent the effectiveness of this incentive approach pushing farmland holder to retain their land are the research questions that will be further elaborated through this research. Observation reveals that incentive system as mandated under Law no 41/2009 is not a new breakthrough and has not relevant with current demand in urban and regional development. This policy is too much rely on local government budget where its affects to the unequal incentive distribution. Moreover this incentive scheme aims to increase productivity whereas in context of Badung, the land productivity tends to decrease as result from narrower land size fragmented by inheritance system.